Characterization of Core Microbiomes and Functional Profiles of Mesophilic Anaerobic Digesters Fed With Chlorella vulgaris Green Microalgae and Maize Silage - Wirth, Roland; Böjti, Tamás; Lakatos, Gergely; Maróti, Gergely; Bagi, Zoltán; Rákhely, Gábor; Kovács, Kornél L. (Frontiers in Energy Research, 2019)
Microalgal biomass is an alternative feedstock for biogas production although its C/N ratio is usually lower than optimal, therefore co-fermentation is recommended. Identification of the core microbiome by metagenome analysis and prediction of functional characteristics are essential to make microalgal feedstock more sustainable and economically feasible. Biogas production from photoautotrophically grown Chlorella vulgaris (Ch. vulgaris) biomass (240 mL CH4 g oTS-1) and co-fermentation with maize silage (330 mL CH4 g oTS-1) has been studied in semi continuous laboratory biogas fermenters. Maize silage control yielded 310 mL CH4 g oTS-1. The microbial community and the read-based functional profiles, derived from these data, were examined during the process by using next-generation metagenome Ion Torrent sequencing technology. The read-based core microbiome consisted of 92 genera from which 60 abundant taxa were directly associated with the microbial methane producing food chain. The data-set was also analyzed in a genome-based approach. 65 bins were assembled, 52 of them belonged in the core biogas producing genera identified by the read-based metagenomes. The read-based and genome-based approaches complemented and verified each other. The functional profiles indicated a variety of glycoside hydrolases. Substantial rearrangements of the methanogen functions have also been observed. Co-fermentation of algal biomass and plant biomass can be carried out for an extended period of time without process failure. The microbial members of the inoculum are well conserved, feedstock composition cause relative abundance changes in the core microbiome.